Learning Climate Support and EFL Students’ Autonomy and Motivation in Online Learning in Indonesia - Norwanto Norwanto; Miftachudin Miftachudin (ELE Reviews: English Language Education Reviews, 2023)
Autonomy, motivation, and learning climate are significant factors in online learning. This study aims to determine the students’ motivation and autonomy in online English as a Foreign Language (EFL) classes. It also classifies the Learning Climate Support (LCS). This quantitative study used the Perceived Locus of Causality Scale for academic motivation in university (PLOC-U) and the Learning Climate Questionnaire (LCQ 15). It involved 134 students from nine universities in Java, Indonesia. The results show that most students were on a moderate level in intrinsic motivation (m=5.25), regulated identification (m=5.74), regulated introjection (m=4.85), and external motivation (m=4.95). The mean of motivation loss was at a low level of 2.73. Most students were ‘regulated identification’ learners, which showed that most students were one step closer to being intrinsic or autonomous learners. Furthermore, LCQ indicated moderate acceptance of lecturers’ empathy and engagement in classes but a lower level of students’ assertiveness. The findings suggest that students did not experience demotivation in online learning, and students’ goals highly motivated students in online learning. The perceived LCS implies the need to improve learning instructions in online classes.